Quantitative study on hepatic genotoxicity of neodymium and its molecular mechanisms based on Benchmark Dose method - Wang, Ning (Frontiers in Pharmacology, 2024)
Neodymium has been shown to induce genotoxicity in mice, but the molecular mechanisms behind this effect are not fully understood. To clarify the genotoxic effects of intragastric administration of neodymium nitrate (Nd(NO3)3) over 28 consecutive days, we assessed the percentage of tail DNA in mouse hepatocytes using the alkaline comet assay, genetic toxicological biomarkers, and the expression levels of genes and proteins related to the p53 pathway in the mouse liver. Our results suggest the potential for accumulation of Nd(NO3)3 in the livers of mice, leading to the formation of micronuclei and DNA double-strand breaks, as indicated by comet and γ-H2AX assays, as well as DNA damage in hepatocytes. Nd(NO3)3 significantly increased the percentage of tail DNA in hepatocytes as measured by the alkaline comet assay and upregulated the expression of molecules related to the p53 pathway, including ATM, Wip1, ATR, Chk2, MDM2, p53, p21, and NF-κB, at both the transcriptional and translational levels. This treatment effectively triggered the production of reactive oxygen species (ROS), 8-hydroxy-2'-deoxyguanosine (8-OHdG), and γ-H2AX in liver tissue. These findings indicate that Nd(NO3)3 induces hepatic genotoxicity and injury in mice, and modulates the expression of genes associated with DNA damage response, carcinogenesis, and inflammatory processes.